Study of clinical efficacy, safety and tolerability of low cost branded generic antiepileptic drugs in children and adolescents - Parekh, Neha Vijay; George, Ruth Susan; Dharmadhikari, Adhiraj; Srivastava, Kavita; Panda, Bijoy Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Generic substitution is preferred to reduce healthcare costs and improve patient adherence. The review of literature showed that physicians all around the world were not comfortable in prescribing generic medications due to the lack of evidence on their safety and efficacy. Methods: A prospective study was conducted over a period of one year in Pune. The patients were categorized on their age and were assessed for the clinical effectiveness data (no. of breakthrough seizures and seizure free days) and safety data (no. of ADR episodes). The mean number of patients controlled and the frequency of adverse events at the 3rd and 6th month were calculated. Results: Authors assessed 150 newly diagnosed pediatric epileptic patients who received anti-epileptic drug monotherapy for at least 6 months, out of which 46 (30.66%) received Oxcarbazepine and 104 (69.33%) received Sodium Valproate. At the end of 3 months of therapy 140 (93.33%) patients were seizure free and 145 (96.66%) patients were seizure free at the end of 6 months. Adverse effects were observed in 14 (30.43) patients on oxcarbazepine and 26 (25%) patients on sodium valproate. The most common adverse effect was weight gain in 34 (22.66%) patients with both the AEDs. Conclusions: Seizure control was achieved in majority of the patients. In addition to the seizure control, the frequency of adverse effects was few and tolerable by the patients when prescribed with low cost branded generics.